2016
DOI: 10.3389/fchem.2016.00008
|View full text |Cite
|
Sign up to set email alerts
|

Surface Analysis of Gold Nanoparticles Functionalized with Thiol-Modified Glucose SAMs for Biosensor Applications

Abstract: In this work, Time of Flight Secondary Ion Mass Spectrometry (ToF-SIMS), Principal Component Analysis (PCA) and X-ray Photoelectron Spectroscopy (XPS) have been used to characterize the surface chemistry of gold substrates before and after functionalization with thiol-modified glucose self-assembled monolayers and subsequent biochemical specific recognition of maltose binding protein (MBP). The results indicate that the surface functionalization is achieved both on flat and nanoparticles gold substrates thus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 68 publications
(67 reference statements)
3
71
0
1
Order By: Relevance
“…However, despite this remarkable difference in sample conditions, XPS is able to provide very useful information on both the surface chemistry and the variation of the surface reactivity and modification of nanomaterials as illustrated in several publications. 25,27,28,34,36,[41][42][43][44]52,69 In the present case, detailed analyses of the C1s high resolution spectra (Fig. S3) show a clear decrease in the component at about 288 eV, which is usually related to the protonated COO À moieties.…”
Section: A Centrifugationmentioning
confidence: 85%
See 1 more Smart Citation
“…However, despite this remarkable difference in sample conditions, XPS is able to provide very useful information on both the surface chemistry and the variation of the surface reactivity and modification of nanomaterials as illustrated in several publications. 25,27,28,34,36,[41][42][43][44]52,69 In the present case, detailed analyses of the C1s high resolution spectra (Fig. S3) show a clear decrease in the component at about 288 eV, which is usually related to the protonated COO À moieties.…”
Section: A Centrifugationmentioning
confidence: 85%
“…[25][26][27] In the case of AuNPs, the use of bifunctionalized thiol molecules is the most straightforward method to covalently bind many different functional groups to the nanoparticles surface. 33,34 Although it has long been known that the high affinity of thiols for noble metals results in the formation of strong and reproducible self-assembled monolayers (ML) on planar surfaces, 35 the presence of stabilizers and/or surfactants in nanoparticles' dispersions may hamper the formation of the Au-S bonds limiting the reaction yield, and thus the reliability and reproducibility of the functionalization process. 36,37 For instance, recent studies have demonstrated that functionalization of citrate-stabilized AuNPs does not lead to a complete displacement of the citrate molecules by the thiols.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the starting AuNPs should not be assumed to be completely "bare", which could be related to the presence of organic shells on solution-synthesized AuNPs and their interactions with PLL chains on the substrate. Assuming a well-defined state for as-received AuNPs that are nominally covered only with a weakly bound citrate shell is notoriously difficult, in part because they can easily become contaminated with other adsorbates at levels detectable by sensitive techniques [34][35][36]. Upon exposure to the ambient environment, adventitious organic contamination will be present on both nominally bare and peptide functionalized gold surfaces in the amounts at least comparable to those of the intentionally immobilized molecules [37,38], thus further diminishing the difference in refractive index surrounding the "bare" vs biofunctionalized AuNPs in the experiments.…”
Section: Ellipsometric Experimental Resultsmentioning
confidence: 99%
“…et al, 2012). Conjugation of maltose binding protein (MBP) to gold nanoparticles funtionalised with thiol-modified glucose (TG) self-assembled monolayers has been studied by Spampinato V. et al (2016). Surface chemistry analysis of the gold nanoparticles before and after functionalisation and interaction with TG and MBP revealed that the reaction of the thiolated gold nanoparticles with MBP occurred with specific amino acid residues exist in the protein binding pocket.…”
Section: Functionalisation Of Nanoparticles With Biomolecules Throughmentioning
confidence: 99%
“…The noble metal nanoparticle, particularly gold (Au) nanoparticle is highly reactive toward thiol group, thus forming a superior Au-S bond. The strong binding affinity of Au towards thiols has been exploited for conjugation of biomolecules such as DNA, peptides, antibodies, and proteins onto the nanoparticle surface (Katz E. and Willner I., 2004;Spampinato V. et al, 2016;Yu M.K. et al, 2012).…”
Section: Functionalisation Of Nanoparticles With Biomolecules Throughmentioning
confidence: 99%